4-((E)-{2-[N-(1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)carboximidoyl]benzylidene}amino)-1,5-dimethyl-2-phenyl-2,3-dihydro-1H-pyrazol-3-one - Potgieter, Kim (International Union of Crystallography, 2011)
The title compound, C(30)H(28)N(6)O(2), is a symmetric diimine derived from ortho-dibenzaldehyde. Both C=N bonds are (E)-configured. The terminal N-bonded phenyl groups adopt staggered conformations relative to their respective parent heterocycles, the relevant least-squares planes intersect at angles of 32.35 (11) and 38.59 (10)°. In the crystal, C—H⋯O contacts connect the molecules into chains along the b axis and give rise to a C (1) (1)(14)C (1) (1)(14) and a R (2) (2)(12) pattern on different levels of graph-set analysis. The shortest intercentroid distance between two centroids was found at 4.2074 (11) Å between the two five-membered heterocycles.